EVALUASI PENYELENGGARAAN MADRASAH UNGGULAN: STUDI KASUS DI MADRASAH IBTIDAIYAH NEGERI (MIN) SERAWI KALIMANTAN SELATAN - FARIDA HANUN (Sekretariat Badan Litbang dan Diklat Kementerian Agama RI, 2017)
This study aims at evaluating the management of Madrasah Unggulan regarding the input, process, andproduct in MIN Serawi, Kalimantan Selatan by employing qualitative design. The results show that: (a) MINSerawi excels in the extra curricular activities, such as: science competition, Rudat arts, and tahlil, (b) departmentof religion in central, city, and regency levels need to conduct coaching, quality assurance and supervision on themanagement of MIN Serawi which is conducted consistently and sustainably, (c) community involvement needs tobe improved in order to attract more sources of funds.KEY WORDS: Evaluation, Management, Madrasah, Unggulan